DEAD-Box Proteins from Escherichia coli Exhibit Multiple ATP-Independent Activities - Zhao, Xinliang (American Society for Microbiology, 2011)
DEAD-box proteins (DBPs) are a widespread class of ATP-dependent RNA helicases that play a key role in unwinding RNA duplexes. In recent years, certain DBPs have also been found to exhibit activities that do not require ATP. To gain a better understanding of prokaryotic RNA metabolism, we investigated whether Escherichia coli DBPs harbor any ATP-independent activities. We show that each of the four E. coli DBPs tested in this study can accelerate the association of cRNA molecules, can stimulate strand displacement, and can function as an RNA chaperone without utilizing ATP. To the best of our knowledge, these prokaryotic DBPs constitute the first examples of proteins that harbor each of these three activities. The identification of these auxiliary functions indicates that the E. coli DBPs are versatile factors that possess significant RNA remodeling activity in addition to their canonical RNA helicase activity and might therefore participate in a greater variety of cellular processes than has been previously appreciated.